Today's challenges - Plasencia Soto, Rommel (2022)
The consensus today is that universities are fundamentally research institutions; rigid teaching and passive transmission of knowledge has taken a healthy turn towards the generation of knowledge and wisdom through (I repeat) research, so that these can then be incorporated into public and private policies to improve the living conditions and well-being of our societies.